1999
DOI: 10.1021/ja9832764
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Ring Closure Energetics and Dynamics of Cyclopentadienyl Manganese Tricarbonyl Derivatives

Abstract: Ring closure following flash photolysis in alkane solvents has been detected for several complexes in the series (η5-C5H4R)Mn(CO)3 where R = COCH3 (1), COCH2SCH3 (2), CO(CH2)2SCH3 (3), COCH2OCH3 (4), (CH2)2CO2CH3 (5), and CH2CO2CH3 (6). In each case where ring closure occurs, a metal CO is ultimately substituted by the side chain functional group. Photoacoustic calorimetry studies reveal that ring closures occur with rate constants faster than 107 s-1 or between 106 and 107 s-1, or in some cases the ring closu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 18 publications
4
51
1
Order By: Relevance
“…These results are in contrast to those for (η 5 -C 5 H 4 R)Mn(CO) 3 , where the quantum yields are found to depend on the side chain structure (R) and in some cases unit quantum yields are observed. 8 Some combination of two mechanisms may account for the quantum yield independence of chain length. First, the quantum yield is determined by the partitioning of the excited states between CO dissociation (0.77) and relaxation back (0.23) to the ground state (no luminescence has been observed for chromium arene tricarbonyls).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in contrast to those for (η 5 -C 5 H 4 R)Mn(CO) 3 , where the quantum yields are found to depend on the side chain structure (R) and in some cases unit quantum yields are observed. 8 Some combination of two mechanisms may account for the quantum yield independence of chain length. First, the quantum yield is determined by the partitioning of the excited states between CO dissociation (0.77) and relaxation back (0.23) to the ground state (no luminescence has been observed for chromium arene tricarbonyls).…”
Section: ■ Discussionmentioning
confidence: 99%
“…For example, we reported that the quantum yields for photoinitiated chelation of manganese cyclopentadienyl tricarbonyl derivatives with different tethered functional groups varied from 0.65 to 1.00. 8 Unit quantum yields demand that every absorbed photon results in CO dissociation with no cage CO recombination. 9 For comparison, the quantum yield for the analogous bimolecular substitution of CpMn(CO) 3 was only 0.65 and was found to be independent of ligand structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both unimolecular and bimolecular pathways for isomerization were observed. This work was followed up by an ultrafast chelation study of [Cr( 6 -C 6 H 5 R)(CO) 3 ], where R is a pendant thioether, and the manganese compound [64][65][66][67]. Time resolved IR spectroscopy reveals both a solvent dependent and solvent free pathway for CO displacement by the thioether on the picosecond to nanosecond timescale.…”
Section: Photochemical Linkage Isomerization In Organometallic Complexesmentioning
confidence: 99%
“…Since the rate constant k 1 describes the rupture of the chelated Co-N bond and the formation of a solvated reaction intermediate, the smallest k 1 value found for 3c implies that the metal-nitrogen bond in 3c is the most difficult one to rupture. The rate of chelate ring closing in coordinatively unsaturated metal complex is known as an ultrafast process and depends on the forming ring size [59][60][61][62]. The solvated ring opened reaction intermediate I S depicted in Scheme 2 are expected to be nearly identical in electronic property of the metal in spite of the different functional groups in their side chains.…”
Section: Resultsmentioning
confidence: 99%